Section8.2Square Root Properties
Â¶In this chapter, we will learn how to both simplify square roots and to do operations with square roots.
Definition8.2.1
If \(y^2=x\) for a positive number \(y\text{,}\) then \(y\) is called the square root of \(x\text{,}\) and we write \(y=\sqrt{x}\text{,}\) where the \(\sqrt{\phantom{x}}\) symbol is called the radical or the root. We call expressions with a root symbol radical expressions. The number inside the radical is called the radicand.
For example, since \(4^2=16\text{,}\) then \(\sqrt{16}=4\text{.}\) Both \(\sqrt{2}\) and \(3\sqrt{2}\) are radical expressions. In both expressions, the number \(2\) is the radicand. You can review the square root basics in SectionÂ 1.3.
The word âradicalâ means something like âon the fringesâ when used in politics, sports, and other places. It actually has that same meaning in math, when you consider a square with area \(A\) as in FigureÂ 8.2.2.
Subsection8.2.1Estimating Square Roots
Â¶When the radicand is a perfect square, its square root is a rational number. If the radicand is not a perfect square, the square root is irrational. We want to be able to estimate square roots without using a calculator.
To estimate \(\sqrt{10}\text{,}\) we can find the nearest perfect squares that are whole numbers on either side of \(10\text{.}\) Recall that the perfect squares are \(1, 4, 9, 16, 25, 36, 49, 64,\dots\) The perfect square that is just below \(10\) is \(9\) and the perfect square just above \(10\) is \(16\text{.}\) This tells us that \(\sqrt{10}\) is between \(\sqrt{9}\) and \(\sqrt{16}\text{,}\) or between \(3\) and \(4\text{.}\) We can also say that \(\sqrt{10}\) is much closer to \(3\) than \(4\) because \(10\) is closer to \(9\text{,}\) so we think \(3.1\) or \(3.2\) would be a good estimate.
To check our estimate, let's find \(\sqrt{10}\) with a calculator:
\begin{equation*} \sqrt{10}\approx3.162 \end{equation*}The actual value is just above \(3\) as we estimated, and between \(3.1\) and \(3.2\text{.}\) Let's look at some more examples.
Exercise8.2.3
Example8.2.4
Estimate \(\sqrt{3.2}\) without a calculator.
The radicand \(3.2\) is between \(1\) and \(4\text{,}\) so \(\sqrt{3.2}\) is between \(\sqrt{1}\) and \(\sqrt{4}\text{,}\) or between \(1\) and \(2\text{.}\)
To be more precise, we notice that \(3.2\) is much closer to \(4\) than \(1\text{.}\) We estimate \(\sqrt{3.2}\) to be about \(1.8\text{.}\)
We will check our estimte with a calculator:
\begin{equation*} \sqrt{3.2}\approx1.788 \end{equation*}Subsection8.2.2Multiplication and Division Properties of Square Roots
Here is an example using perfect squares and the rules of exponents to show a relationship between the product of two square roots:
\begin{gather*} \sqrt{9\cdot16}=\sqrt{3^2\cdot 4^2}=\sqrt{(3\cdot4)^2}=3\cdot4=12\\ \end{gather*}and
\begin{gather*} \sqrt{9}\cdot\sqrt{16}=\sqrt{3^2}\cdot\sqrt{4^2}=3\cdot4=12 \end{gather*}Whether we multiply the radicands first or take the square roots first, we get the same result. This tells us that in multiplication with radicals, we can combine factors into a single radical or separate them as needed.
Now let's look at division. When we learned how to find the square root of a fraction in SectionÂ 1.3, we saw that the numerators and denominators could be simplified separately. We multiply the numerators and denominators independently. Here is an example of two different ways to simplify a fraction in a square root:
\begin{gather*} \sqrt{\frac{25}{9}}=\sqrt{\left(\frac{5}{3}\right)^2}=\frac{5}{3}\\ \end{gather*}and
\begin{gather*} \frac{\sqrt{25}}{\sqrt{9}}=\frac{\sqrt{5^2}}{\sqrt{3^2}}=\frac{5}{3} \end{gather*}Just like with multiplication, we can separate the numerators and denominators in a radical expression or combine them as needed. Note that we worked with expressions that were perfect squares, but these properties will work regardless of the number inside the radical. Let's summarize these properties.
Fact8.2.5Multiplication and Division Properties of Square Roots
For any positive real numbers \(x\) and \(y\) we have the following properties:
 Multiplication Property of Square Roots
\(\sqrt{x\cdot y}=\sqrt{x}\cdot\sqrt{y}\)
 Division Property of Square Roots
\(\sqrt{\frac{x}{y}}=\frac{\sqrt{x}}{\sqrt{y}}\)
Subsection8.2.3Simplifying Square Roots
We can use Multiplication and Division Properties of Square Roots to simplify a radicand that is not a perfect square. Simplifying radicals is similar to simplifying fractions because we want the radicand to be as small as possible.
To understand why we can simplify radicals, let's use a calculator to compare \(\sqrt{12}\) and \(2\sqrt{3}\text{.}\)
\begin{align*} \sqrt{12}\amp=3.4641\ldots \amp\amp\text{and}\amp2\sqrt{3}\amp=3.4641\ldots \end{align*}These are equivalent expressions so let's see how we can simplify \(\sqrt{12}\) to \(2\sqrt{3}\text{.}\)
First, we will make a table of factor pairs for the number \(12\text{,}\) as we did in SectionÂ 7.3.
\begin{align*} 1\amp\cdot12\\ 2\amp\cdot6\\ 3\amp\cdot4 \end{align*}The factor pair with the largest perfect square is \(3\cdot4\text{.}\) We will use the property of multiplying radicals to separate the perfect square from the other factor. We write the perfect square first because it will end up in front of the radical.
\begin{align*} \sqrt{12}\amp=\sqrt{4}\cdot\sqrt{3}\\ \amp=2\cdot\sqrt{3}\\ \amp=2\sqrt{3} \end{align*}This process can be used to simplify any square root, or to determine that it is fully simplified. Let's look at a few more examples.
Example8.2.6
Simplify \(\sqrt{72}\text{.}\)
Here is a table of factor pairs for the number \(72\text{.}\)
\begin{align*} 1\amp\cdot72\amp4\amp\cdot18\\ 2\amp\cdot36\amp6\amp\cdot12\\ 3\amp\cdot24\amp8\amp\cdot9 \end{align*}The largest perfect square is \(36\) so we will rewrite \(72\) as \(36\cdot2\text{.}\)
\begin{align*} \sqrt{72}\amp=\sqrt{36\cdot2}\\ \amp=\sqrt{36}\cdot\sqrt{2}\\ \amp=6\sqrt{2} \end{align*}Notice that if we had chosen \(4\cdot18\) we could simplify the radical partially but we would need to continue and find the perfect square of \(9\) in \(18\text{.}\)
Exercise8.2.7
Example8.2.8
Simplify \(\sqrt{30}\text{.}\)
Here is a table of factor pairs for the number \(30\text{.}\)
\begin{align*} 1\amp\cdot30\amp3\amp\cdot10\\ 2\amp\cdot15\amp5\amp\cdot6 \end{align*}The number \(30\) does not have any factors that are perfect squares so it cannot be simplifed further.
We can also use Division Property of Square Roots to simplify expressions.
Example8.2.9
Simplify \(\sqrt{\frac{9}{16}}\text{.}\)
Simplify \(\frac{\sqrt{50}}{\sqrt{2}}\text{.}\)

For the first expression, we will use the Division Property of Square Roots:
\begin{align*} \sqrt{\frac{9}{16}}\amp=\frac{\sqrt{9}}{\sqrt{16}}\\ \amp=\frac{3}{4} \end{align*} 
For the second expression, we use the same property in reverse: \(\frac{\sqrt{x}}{\sqrt{y}}=\sqrt{\frac{x}{y}}\text{:}\)
\begin{align*} \frac{\sqrt{50}}{\sqrt{2}}\amp=\sqrt{\frac{50}{2}}\\ \amp=\sqrt{25}\\ \amp=5 \end{align*}
Subsection8.2.4Multiplying Square Root Expressions
If we use the Multiplication Property of Square Roots and the Division Property of Square Roots in the reverse order as
\begin{align*} \sqrt{x}\cdot\sqrt{y}\amp=\sqrt{xy}\amp\amp \text{and}\amp \frac{\sqrt{x}}{\sqrt{y}}\amp=\sqrt{\frac{x}{y}}\text{,} \end{align*}we can use these properties to multiply and divide square root expressions. We want to simplify each radical first to keep the radicands as small as possible. Let's look at a few examples.
Example8.2.10
Multiply \(\sqrt{8}\cdot\sqrt{54}\text{.}\)
We will simplify each radical first, and then multiply them together. We do not want to multiply \(8\cdot54\) because we will end up with a larger number that is harder to factor.
\begin{align*} \sqrt{8}\cdot\sqrt{54}\amp=\sqrt{4\cdot2}\cdot\sqrt{9\cdot6}\\ \amp=2\sqrt{2}\cdot3\sqrt{6}\\ \amp=2\cdot3\sqrt{2\cdot6}\\ \amp=2\cdot3\sqrt{2\cdot2\cdot3}\\ \amp=6\cdot2\sqrt{3}\\ \amp=12\sqrt{3} \end{align*}We could have multiplied \(2\cdot6\) inside the radical to get \(12\) and then factored \(12\) into \(4\cdot3\text{.}\) Whenever you find a pair of identical factors, this is a perfect square.
Exercise8.2.11
Example8.2.12
Multiply \(\sqrt{\frac{6}{5}}\cdot\sqrt{\frac{3}{5}}\text{.}\)
Subsection8.2.5Adding and Subtracting Square Root Expressions
We learned the Multiplication Property of Square Roots previously and applied this to multiplication of square roots, but we cannot apply this property to the operations of addition or subtraction. Here are two examples to demonstrate this:
\begin{align*} \sqrt{9+16}\amp\stackrel{?}{=}\sqrt{9}+\sqrt{16}\amp\sqrt{16925}\amp\stackrel{?}{=}\sqrt{169}\sqrt{25}\\ \sqrt{25}\amp\stackrel{?}{=}3+4\amp\sqrt{144}\amp\stackrel{?}{=}135\\ 5\amp\stackrel{no}{=}7\amp12\amp\stackrel{no}{=}8 \end{align*}We do not get the same result if we separate the radicals, so we must complete any additions and subtractions inside the radical first.
To add and subtract radical expressions, we will need to recognize that we can only add and subtract like terms. In this case, we will call them like radicals. In fact, adding like radicals will work just like adding like terms
\begin{align*} x+x\amp=2x\\ \end{align*}and
\begin{align*} \sqrt{5}+\sqrt{5}\amp=2\sqrt{5} \end{align*}We can verify that the second equation is true by replacing \(x\) with \(\sqrt{5}\) in the second equation. Let's look at a few more examples.
Example8.2.13
Simplify \(\sqrt{2}+\sqrt{8}\text{.}\)
To help understand \(\sqrt{2}+2\sqrt{2}=3\sqrt{2}\text{,}\) think of \(x+2x=3x\) or âa taco plus two tacos is three tacos.â
Exercise8.2.14
Example8.2.15
Simplify \(\sqrt{2}+\sqrt{27}\text{.}\)
We cannot simplify the expression further because \(\sqrt{2}\) and \(\sqrt{3}\) are not like radicals.
Example8.2.16
Simplify \(\sqrt{6}\sqrt{18}\cdot\sqrt{12}\text{.}\)
In this example, we should multiply the latter two suqare roots first and then see if we have like radicals.
\begin{align*} \sqrt{6}\sqrt{18}\cdot\sqrt{12}\amp=\sqrt{6}\sqrt{9\cdot2}\cdot\sqrt{4\cdot3}\\ \amp=\sqrt{6}3\sqrt{2}\cdot2\sqrt{3}\\ \amp=\sqrt{6}3\cdot2\cdot\sqrt{2}\cdot\sqrt{3}\\ \amp=\sqrt{6}6\sqrt{6}\\ \amp=5\sqrt{6} \end{align*}Subsection8.2.6Rationalizing the Denominator
When simplifying square root expressions, we have seen that we need to make the radicand as small as possible. Another rule is that we do not leave any irrational numbers, such as \(\sqrt{3}\) or \(2\sqrt{5}\text{,}\) in the denominator of a fraction. In other words, we want the denominator to be rational. The process of dealing with such numbers in the denominator is called rationalizing the denominator.
Let's see how we can remove the square root symbol from the denominator in \(\frac{1}{\sqrt{5}}\text{.}\) If we multiply a radical by itself, the result is the radicand, by DefintionÂ 8.2.1. As an example:
\begin{equation*} \sqrt{5}\cdot\sqrt{5}=5 \end{equation*}To write \(\frac{1}{\sqrt{5}}\) as an equivalent fraction, we must multiply both the numerator and denominator by the same number. If we multiply the numerator and denominator by \(\sqrt{5}\text{,}\) we have:
\begin{align*} \frac{1}{\sqrt{5}}\amp=\frac{1}{\sqrt{5}} \multiplyright{\frac{\sqrt{5}}{\sqrt{5}}}\\ \amp=\frac{1\cdot\sqrt{5}}{\sqrt{5}\cdot\sqrt{5}}\\ \amp=\frac{\sqrt{5}}{5} \end{align*}We can use a calculator to verify that \(\frac{1}{\sqrt{5}}=\frac{\sqrt{5}}{5}\text{.}\) They both are \(0.4472\ldots\text{.}\) Let's look at a few more examples.
Example8.2.17
Rationalize the denominator in \(\frac{6}{\sqrt{3}}\text{.}\)
We will rationalize this denominator by multiplying the numerator and denominator by \(\sqrt{3}\text{:}\)
\begin{align*} \frac{6}{\sqrt{3}}\amp=\frac{6}{\sqrt{3}}\multiplyright{\frac{\sqrt{3}}{\sqrt{3}}}\\ \amp=\frac{6\cdot\sqrt{3}}{\sqrt{3}\cdot\sqrt{3}}\\ \amp=\frac{6\sqrt{3}}{3}\\ \amp=2\sqrt{3} \end{align*}Note that we reduced any fractions that are outside the radical.
Exercise8.2.18
Example8.2.19
Rationalize the denominator in \(\sqrt{\frac{2}{7}}\text{.}\)
Subsection8.2.7More Complicated Square Root Operations
Â¶In SectionÂ 6.3, we learned how to multiply polynomials like \(2(x+3)\) and \((x+2)(x+3)\text{.}\) All the methods we learned apply when we multiply square root expressions. We will look at a few examples done with different methods.
Example8.2.20
Multiply \(\sqrt{5}(\sqrt{3}\sqrt{2})\text{.}\)
We will use the distributive property to do this problem:
\begin{align*} \sqrt{5}(\sqrt{3}\sqrt{2})\amp=\sqrt{5}\sqrt{3}\sqrt{5}\sqrt{2}\\ \amp=\sqrt{15}\sqrt{10} \end{align*}Example8.2.21
Multiply \((\sqrt{6}+\sqrt{12})(\sqrt{3}\sqrt{2})\text{.}\)
We will use the FOIL Method to do this problem:
\begin{align*} (\sqrt{6}+\sqrt{12})(\sqrt{3}\sqrt{2})\amp=\sqrt{6}\sqrt{3}\sqrt{6}\sqrt{2}+\sqrt{12}\sqrt{3}\sqrt{12}\sqrt{2}\\ \amp=\sqrt{18}\sqrt{12}+\sqrt{36}\sqrt{24}\\ \amp=3\sqrt{2}2\sqrt{3}+62\sqrt{6} \end{align*}When simplifying radicals it is useful to keep in mind that for any \(x\ge 0\text{,}\)
\begin{equation*} \sqrt{x}\cdot\sqrt{x}=x\text{.} \end{equation*}Example8.2.22
Expand \((\sqrt{3}\sqrt{2})^2\text{.}\)
We will use the FOIL method to expand this expression:
\begin{align*} (\sqrt{3}\sqrt{2})^2\amp=(\sqrt{3}\sqrt{2})(\sqrt{3}\sqrt{2})\\ \amp=(\sqrt{3})^2\sqrt{3}\sqrt{2}\sqrt{2}\sqrt{3}+(\sqrt{2})^2\\ \amp=3\sqrt{6}\sqrt{6}+2\\ \amp=52\sqrt{6} \end{align*}Example8.2.23
Multiply \((\sqrt{5}\sqrt{7})(\sqrt{5}+\sqrt{7})\text{.}\)
We will again use the FOIL method to expand this expression, but will note that it is a special form \((ab)(a+b)\) and will simplify to \(a^2b^2\text{:}\)
\begin{align*} (\sqrt{5}\sqrt{7})(\sqrt{5}+\sqrt{7})\amp=(\sqrt{5})^2+\sqrt{5}\sqrt{7}\sqrt{7}\sqrt{5}(\sqrt{7})^2\\ \amp=5+\sqrt{35}\sqrt{35}7\\ \amp=2 \end{align*}Subsection8.2.8Exercises
Square Roots and Perfect Squares
1
Which of the following are square numbers? There may be more than one correct answer.
\(124\)
\(16\)
\(97\)
\(2\)
\(36\)
\(4\)
2
Which of the following are square numbers? There may be more than one correct answer.
\(1\)
\(72\)
\(100\)
\(58\)
\(9\)
\(122\)
3
Find the square root of the following numbers:
\(\displaystyle{ \sqrt{16} }\) =
\(\displaystyle{ \sqrt{81} }\) =
\(\displaystyle{ \sqrt{4} }\) =
4
Find the square root of the following numbers:
\(\displaystyle{ \sqrt{36} }\) =
\(\displaystyle{ \sqrt{16} }\) =
\(\displaystyle{ \sqrt{64} }\) =
5
Find the square root of the following numbers.
\(\displaystyle{ \sqrt{{{\frac{49}{144}}}} }\) =
\(\displaystyle{ \sqrt{{{\frac{121}{36}}}} }\) =
6
Find the square root of the following numbers.
\(\displaystyle{ \sqrt{{{\frac{64}{49}}}} }\) =
\(\displaystyle{ \sqrt{{{\frac{16}{9}}}} }\) =
7
Find the square root of the following numbers without using a calculator.
\(\displaystyle{ \sqrt{100} }\) =
\(\displaystyle{ \sqrt{1} }\) =
\(\displaystyle{ \sqrt{10000} }\) =
8
Find the square root of the following numbers without using a calculator.
\(\displaystyle{ \sqrt{121} }\) =
\(\displaystyle{ \sqrt{1.21} }\) =
\(\displaystyle{ \sqrt{12100} }\) =
9
Find the square root of the following numbers without using a calculator.
\(\displaystyle{ \sqrt{144} }\) =
\(\displaystyle{ \sqrt{14400} }\) =
\(\displaystyle{ \sqrt{1440000} }\) =
10
Find the square root of the following numbers without using a calculator.
\(\displaystyle{ \sqrt{4} }\) =
\(\displaystyle{ \sqrt{400} }\) =
\(\displaystyle{ \sqrt{40000} }\) =
11
Find the square root of the following numbers without using a calculator.
\(\displaystyle{ \sqrt{9} }\) =
\(\displaystyle{ \sqrt{0.09} }\) =
\(\displaystyle{ \sqrt{0.0009} }\) =
12
Find the square root of the following numbers without using a calculator.
\(\displaystyle{ \sqrt{16} }\) =
\(\displaystyle{ \sqrt{0.16} }\) =
\(\displaystyle{ \sqrt{0.0016} }\) =
Estimation
13
Without using a calculator, estimate the value of \(\sqrt{48}\text{:}\)
6.93
7.07
7.93
6.07
14
Without using a calculator, estimate the value of \(\sqrt{52}\text{:}\)
7.21
7.79
6.21
6.79
Simplify Radical Expressions
15
Simplify the radical expression or state that it is not a real number.
\(\sqrt{\frac{64}{81}}\) is .
16
Simplify the radical expression or state that it is not a real number.
\(\sqrt{\frac{81}{100}}\) is .
17
Simplify the radical expression or state that it is not a real number.
\(\sqrt{121}\) is .
18
Simplify the radical expression or state that it is not a real number.
\(\sqrt{144}\) is .
19
Simplify the radical expression or state that it is not a real number.
\(\sqrt{9}\) is .
20
Simplify the radical expression or state that it is not a real number.
\(\sqrt{16}\) is .
21
Simplify the radical expression or state that it is not a real number.
\(\sqrt{{{\frac{16}{25}}}}\) is .
22
Simplify the radical expression or state that it is not a real number.
\(\sqrt{{{\frac{25}{121}}}}\) is .
23
Simplify the radical expression or state that it is not a real number.
\(\sqrt{{{\frac{36}{49}}}}\) is .
24
Simplify the radical expression or state that it is not a real number.
\(\sqrt{{{\frac{64}{121}}}}\) is .
25
Simplify the radical expression or state that it is not a real number.
\(\displaystyle{ \frac{{\sqrt{50}}}{{\sqrt{2}}} =}\)
26
Simplify the radical expression or state that it is not a real number.
\(\displaystyle{ \frac{{\sqrt{180}}}{{\sqrt{5}}} =}\)
27
Simplify the radical expression or state that it is not a real number.
\(\displaystyle{ \frac{{\sqrt{3}}}{{\sqrt{108}}} =}\)
28
Simplify the radical expression or state that it is not a real number.
\(\displaystyle{ \frac{{\sqrt{6}}}{{\sqrt{24}}} =}\)
29
Simplify the radical expression or state that it is not a real number.
\(\displaystyle{ {\sqrt{75}} = }\)
30
Simplify the radical expression or state that it is not a real number.
\(\displaystyle{ {\sqrt{45}} = }\)
31
Simplify the radical expression or state that it is not a real number.
\(\displaystyle{ {\sqrt{1125}} = }\)
32
Simplify the radical expression or state that it is not a real number.
\(\displaystyle{ {\sqrt{1176}} = }\)
33
Simplify the radical expression or state that it is not a real number.
\(\displaystyle{ {\sqrt{231}} = }\)
34
Simplify the radical expression or state that it is not a real number.
\(\displaystyle{ {\sqrt{154}} = }\)
35
Simplify the radical expression or state that it is not a real number.
\(\displaystyle{\sqrt{169}\sqrt{144}=}\)
\(\displaystyle{\sqrt{169144}=}\)
36
Simplify the radical expression or state that it is not a real number.
\(\displaystyle{\sqrt{169}\sqrt{144}=}\)
\(\displaystyle{\sqrt{169144}=}\)
Multiplying Square Root Expressions
37
Simplify the expression.
\(2\sqrt{7} \cdot 8\sqrt{2}=\)
38
Simplify the expression.
\(3\sqrt{13} \cdot 6\sqrt{11}=\)
39
Simplify the expression.
\(4\sqrt{3} \cdot 3\sqrt{{4}} =\)
40
Simplify the expression.
\(5\sqrt{7} \cdot 8\sqrt{{25}} =\)
41
Simplify the expression.
\(\displaystyle{4\sqrt{10} \cdot 3\sqrt{45}=}\)
42
Simplify the expression.
\(\displaystyle{4\sqrt{5} \cdot 2\sqrt{40}=}\)
43
Simplify the expression.
\(\displaystyle{ {\sqrt{3}} \cdot {8\sqrt{27}} = }\)
44
Simplify the expression.
\(\displaystyle{ {\sqrt{5}} \cdot {3\sqrt{20}} = }\)
45
Simplify the expression.
\(\displaystyle{ \sqrt{\frac{1}{10}} \cdot \sqrt{\frac{3}{10}} =}\)
46
Simplify the expression.
\(\displaystyle{ \sqrt{\frac{5}{2}} \cdot \sqrt{\frac{1}{2}} =}\)
47
Simplify the expression.
\(\displaystyle{ {\sqrt{\frac{6}{13}}} \cdot {\sqrt{\frac{2}{13}}} =}\)
48
Simplify the expression.
\(\displaystyle{ {\sqrt{\frac{6}{19}}} \cdot {\sqrt{\frac{3}{19}}} =}\)
Adding and Subtracting Square Root Expressions
49
Simplify the expression.
\(\displaystyle{{14\sqrt{11}}  {15\sqrt{11}} =}\)
50
Simplify the expression.
\(\displaystyle{{15\sqrt{6}}  {16\sqrt{6}} =}\)
51
Simplify the expression.
\(\displaystyle{{17\sqrt{23}}  {20\sqrt{23}} + {11\sqrt{23}} =}\)
52
Simplify the expression.
\(\displaystyle{{18\sqrt{15}}  {17\sqrt{15}} + {15\sqrt{15}} =}\)
53
Simplify the expression.
\(\displaystyle{{\sqrt{63}} + {\sqrt{252}} =}\)
54
Simplify the expression.
\(\displaystyle{{\sqrt{252}} + {\sqrt{63}} =}\)
55
Simplify the expression.
\(\displaystyle{{\sqrt{50}} + {\sqrt{8}} + {\sqrt{108}} + {\sqrt{27}} =}\)
56
Simplify the expression.
\(\displaystyle{{\sqrt{8}} + {\sqrt{18}} + {\sqrt{48}} + {\sqrt{27}} =}\)
57
Simplify the expression.
\(\displaystyle{{\sqrt{147}}  {\sqrt{75}} =}\)
58
Simplify the expression.
\(\displaystyle{{\sqrt{125}}  {\sqrt{20}} =}\)
59
Simplify the expression.
\(\displaystyle{{\sqrt{180}}  {\sqrt{45}}  {\sqrt{8}}  {\sqrt{72}} =}\)
60
Simplify the expression.
\(\displaystyle{{\sqrt{294}}  {\sqrt{24}}  {\sqrt{20}}  {\sqrt{45}} =}\)
Rationalizing the Denominator
61
Rationalize the denominator and simplify the expression.
\(\displaystyle{\frac{7}{\sqrt{{36}}}}\) = .
62
Rationalize the denominator and simplify the expression.
\(\displaystyle{\frac{9}{\sqrt{{64}}}}\) = .
63
Rationalize the denominator and simplify the expression.
\(\displaystyle{ \frac{1}{\sqrt{10}} = }\)
64
Rationalize the denominator and simplify the expression.
\(\displaystyle{ \frac{1}{\sqrt{2}} = }\)
65
Rationalize the denominator and simplify the expression.
\(\displaystyle{ \frac{10}{\sqrt{3}} = }\)
66
Rationalize the denominator and simplify the expression.
\(\displaystyle{ \frac{8}{\sqrt{3}} = }\)
67
Rationalize the denominator and simplify the expression.
\(\displaystyle{ \frac{9}{5\sqrt{5}} = }\)
68
Rationalize the denominator and simplify the expression.
\(\displaystyle{ \frac{5}{9\sqrt{6}} = }\)
69
Rationalize the denominator and simplify the expression.
\(\displaystyle{ \frac{15}{\sqrt{21}} = }\)
70
Rationalize the denominator and simplify the expression.
\(\displaystyle{ \frac{9}{\sqrt{30}} = }\)
71
Rationalize the denominator and simplify the expression.
\(\displaystyle{ \frac{10}{\sqrt{10}} = }\)
72
Rationalize the denominator and simplify the expression.
\(\displaystyle{ \frac{40}{\sqrt{10}} = }\)
73
Rationalize the denominator and simplify the expression.
\(\displaystyle{ \frac{1}{{\sqrt{12}}} = }\)
74
Rationalize the denominator and simplify the expression.
\(\displaystyle{ \frac{1}{{\sqrt{28}}} = }\)
75
Rationalize the denominator and simplify the expression.
\(\displaystyle{ \frac{9}{{\sqrt{180}}} = }\)
76
Rationalize the denominator and simplify the expression.
\(\displaystyle{ \frac{6}{{\sqrt{48}}} = }\)
77
Rationalize the denominator and simplify the expression.
\(\displaystyle{ \sqrt{\frac{11}{36}} = }\)
78
Rationalize the denominator and simplify the expression.
\(\displaystyle{ \sqrt{\frac{10}{49}} = }\)
79
Rationalize the denominator and simplify the expression.
\(\displaystyle{ \sqrt{\frac{81}{2}} = }\)
80
Rationalize the denominator and simplify the expression.
\(\displaystyle{ \sqrt{\frac{81}{2}} = }\)
81
Rationalize the denominator and simplify the expression.
\(\displaystyle{ \sqrt{\frac{15}{11}} = }\)
82
Rationalize the denominator and simplify the expression.
\(\displaystyle{ \sqrt{\frac{2}{5}} = }\)
83
Rationalize the denominator and simplify the expression.
\(\displaystyle{ \sqrt{\frac{28}{11}} = }\)
84
Rationalize the denominator and simplify the expression.
\(\displaystyle{ \sqrt{\frac{45}{11}} = }\)
More Complicated Square Root Operations
85
Expand and simplify the expression.
\(\displaystyle{{\sqrt{2}} \left({\sqrt{3}} + {\sqrt{5}}\right) =}\)
86
Expand and simplify the expression.
\(\displaystyle{{\sqrt{7}} \left({\sqrt{19}} + {\sqrt{17}}\right) =}\)
87
Expand and simplify the expression.
\(\displaystyle{(6 + {\sqrt{11}})(4 + {\sqrt{11}}) =}\)
88
Expand and simplify the expression.
\(\displaystyle{(3 + {\sqrt{11}})(7 + {\sqrt{11}}) =}\)
89
Expand and simplify the expression.
\(\displaystyle{(9  {\sqrt{7}})(5  5 {\sqrt{7}}) =}\)
90
Expand and simplify the expression.
\(\displaystyle{(6  {\sqrt{7}})(3  3 {\sqrt{7}}) =}\)
91
Expand and simplify the expression.
\(\displaystyle{ (1+\sqrt{2})^2 =}\)
92
Expand and simplify the expression.
\(\displaystyle{ (2+\sqrt{6})^2 =}\)
93
Expand and simplify the expression.
\(\displaystyle{ (\sqrt{3}3)^2 =}\)
94
Expand and simplify the expression.
\(\displaystyle{ (\sqrt{2}4)^2 =}\)
95
Expand and simplify the expression.
\(\displaystyle{ (\sqrt{15}  \sqrt{5})^2 =}\)
96
Expand and simplify the expression.
\(\displaystyle{ (\sqrt{15}  \sqrt{5})^2 =}\)
97
Expand and simplify the expression.
\(\displaystyle{\left(10  3 {\sqrt{7}}\right)^2 =}\)
98
Expand and simplify the expression.
\(\displaystyle{\left(8  9 {\sqrt{7}}\right)^2 =}\)
99
Expand and simplify the expression.
\(\displaystyle{(5  {\sqrt{13}})(5 + {\sqrt{13}}) =}\)
100
Expand and simplify the expression.
\(\displaystyle{(10  {\sqrt{5}})(10 + {\sqrt{5}}) =}\)
101
Expand and simplify the expression.
\(\displaystyle{({\sqrt{5}} + {\sqrt{11}})({\sqrt{5}}  {\sqrt{11}}) =}\)
102
Expand and simplify the expression.
\(\displaystyle{({\sqrt{6}} + {\sqrt{11}})({\sqrt{6}}  {\sqrt{11}}) =}\)
103
Expand and simplify the expression.
\(\displaystyle{({4\sqrt{7}} + {7\sqrt{6}})({4\sqrt{7}}  {7\sqrt{6}}) =}\)
104
Expand and simplify the expression.
\(\displaystyle{({5\sqrt{5}} + {3\sqrt{7}})({5\sqrt{5}}  {3\sqrt{7}}) =}\)